Biomechanics of the lead straight punch and related indexes between sanda fighters and boxers from the perspective of cross-border talent transfer - Liu, Y.; Li, L.; Yan, L.; He, X.; Zhao, B. (Frontiers in Physiology, 2023)
Objective: To bridge the technical gaps in reserve athletes in China`s national boxing program and to rapidly improve the overall level of boxing, the Wushu Sports Administration Center of the General Administration of Sports of China has sent outstanding Sanda players to boxing events through cross-border talent transfer. This was done to widely improve the strengths and resources in various fields to prepare for the Tokyo Olympic Games. In view of this, we analyzed and compared differences in biomechanical parameters of the lead straight punch and index of force developments of the lower extremities between Sanda and boxing. The results provide information and insights to bridge the technical gaps in cross-border talent transfer from Sanda to boxing.